TINJAUAN PENAMBAHAN ASBUTON DALAM CAMPURAN BERASPAL PANAS DARI SEGI TEKNIS DAN FINANSIAL - Kurniadji Kurniadji; Nono Nono (Direktorat Bina Teknik Jalan dan Jembatan, 2006)
Recent years, there have been two issues of asphalt pavement in Indonesia i.e firstly, the supply of asphalt cannot meet national demand, so that it needs to be imported. Secondly, life design cannot be reached due to early demage resulted from inappropriate mixture used to accommodate traffic loads. To reduce imported asphalt and improve asphalt mixture performance is the use of asbuton known as Butas, mined in Buton where 677 million tonnes of natural asphalt deposit can be found which equivalent to 170 million tonnes of asphalt cement. Lawele has the most asbuton constituting 30% or 210 million tonnes but has not been utilized, on the other hand Kabungka with deposit of 60 million tonnes has been first developed. Asbuton Lawele contains 30% of bitumen, by considering the ratio of bitumen filler, the use of asphalt cement in mixture can be saved to one third resulting in saving of imported asphalt from 600.000 tonnes to 400.000 tonnes or saving of 100 million per year. Research result showed that hot mix asphalt added by asbuton has several advantages mainly in the increase of dynamic stability from 1457 passes/mm to 2743 passes/mm with 5% asbuton, 3283 passes/mm of 10% asbuton and resilient modulus from 2302 MPa without asbuton to 3480 MPa with 5% of as buton and 5163 MPa with 10% of asbuton. Moreone, from simulation calculation based on existing road condition and given resilient modulus of asphalt mix, as the thickness is less with the same design life and cumulative traffic load, the construction of asphalt layers with asbuton is 20% cheaper compared to asphalt layers without asbuton, although the price unit in ton is 3,7% higher for 5% of asbuton and 7,3% for 10% of asbut on, the price of asbuton is Rp. 750.000 perton. In order to have equivalent price between hot asphalt mix with asbuton and without asbuton, the price of asbuton should be Rp. 540.000 per ton in project location.